Biomimetic intelligent nanoplatform with cascade amplification effect for tumor synergy therapy - Ying Wang; Qing Ji; Chao Yan; Pang Ji (Scientific Reports)
Abstract Tumor heterogeneity, immune-suppressive microenvironment and the precise killing of tumor cells by drugs are important factors affecting tumor treatment. In this study, we developed environment-responsive drug delivery system (FM@IQ/PST&ZIF-8/DOX) based on ZIF-8 for tumor photothermal/immunotherapy/chemotherapy synergistic therapy. The prepared FM@IQ/PST&ZIF-8/DOX nanoplatfrom not only has highly drug loading capacity for chemotherapeutic drug-doxorubicin, but also erythrocyte membrance modified on their surface can endow their immunity-escaping property and prolong their blood circulation time. More important, the neurotransmitter serotonin was encapsulated on the surface of ZIF-8/DOX by oxidative polymerization, which can effectively avoid the premature leakage of DOX in the blood circulation. And the formed polyserotonin shell has superior photothermal conversion performance, as well as the adsorption property of polyserotonin shell was utilized to load imiqumod. When FM@IQ/PST&ZIF-8/DOX entered the tumor tissue, the surface modified folate molecules can specifically bind to the folate receptors on the surface of tumor cells to improve FM@IQ/PST&ZIF-8/DOX uptake by tumor cells. In vitro and in vivo results showed that FM@IQ/PST&ZIF-8/DOX nanoplatform could generate a large amount of heat under near-infrared light irradiation, and then induce the apoptosis of tumor cells, release tumor associated antigens, and effectively solve the problem of tumor heterogeneity. In addition, the loaded imiquimod could effectively improve the immunosuppressive microenvironment, enhance the body’s anti-tumor immune response, to inhibit tumor metastasis and recurrence. Therefore, the novel FM@IQ/PST&ZIF-8/DOX nanoplatform designed in this research can not only achieve controllable and precise drug release, but also it is expected to become a promising new strategy for tumor treatment and provide corresponding inspiration for the later research and development of environment-responsive drugs.